2017
DOI: 10.3961/jpmph.16.101
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Financial Crisis on Lifestyle Health Determinants Among Older Adults Living in the Mediterranean Region: The Multinational MEDIS Study (2005-2015)

Abstract: ObjectivesBy the end of the 2000s, the economic situation in many European countries started to deteriorate, generating financial uncertainty, social insecurity and worse health status. The aim of the present study was to investigate how the recent financial crisis has affected the lifestyle health determinants and behaviours of older adults living in the Mediterranean islands.MethodsFrom 2005 to 2015, a population-based, multi-stage convenience sampling method was used to voluntarily enrol 2749 older adults (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
1
19
0
2
Order By: Relevance
“…Thus, tobacco prevention strategies should mainly target these smoking groups [67]. Generally, a shift towards less healthy behaviour was noticeable after the economic crisis, as has been observed in two recent Greek studies [72,73].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
“…Thus, tobacco prevention strategies should mainly target these smoking groups [67]. Generally, a shift towards less healthy behaviour was noticeable after the economic crisis, as has been observed in two recent Greek studies [72,73].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 99%
“…Studies have shown that financial crises and subsequent responses can negatively affect the health of groups that are already facing problems accessing health care services (see for example, Kentikelenis et al, 2015, on the increased infectious disease risks among migrant populations in Europe; and Foscolou et al, 2017, on the increased isolation, smoking, depressive symptoms and adoption of less healthy dietary habits by older people). Due to the global recession and the deterioration of the welfare state, neoliberal regulations are often adopted in the area of health, leading to the loss of the notion that health is a universal right.…”
Section: Austerity-driven Reforms and The Construction Of Long-lastinmentioning
confidence: 99%
“…10 Economic crises can also affect lifestyle behaviors such as physical activity levels, television-viewing and diet. 11,12 Consequently, adoption of unhealthy lifestyles can also be correlated with negative mental health outcomes. 7,13,14 Given the ecological approach adopted, we do not intend to establish causality between economic crises, health-related behaviors and hospitalizations due to affective disorders.…”
Section: Discussionmentioning
confidence: 99%